Collaborative Governance for Resilience (CORE) Model in Addressing Rice Security Issues in Banten Province, Indonesia - Muhammad Ibrahim Rantau; Soviyan Munawar; Hilman; Tb.Yudi Muhtadi; Irvan Arif Kurniawan (Ilomata International Journal of Management, 2026)
Agricultural production data for Banten Province, particularly unhusked rice, indicates a positive upward trend over the past three years, with a rice surplus reaching 76,133 tons by the end of June 2025. However, classic anomalies related to the rice distribution supply chain system persist. Premium and medium-grade rice prices remain high, often stockout from the market, as happened after the harvest season in August 2025. Distributors frequently produce adulterated rice to reduce production costs. Meanwhile, stakeholders involved in the distribution supply system, particularly small milling industries, small distributors, and unhusked rice processing industries, have experienced a decline in production, with many even ceasing operations. This study aims to identify issues within the rice distribution supply chain system and propose an appropriate governance model to address these issues. This article is the result of field research with a descriptive qualitative approach, where data collection methods was carried out by observation, analysis documentation study, in-depth interviews, and focus group discussions (FGDs). The results indicate that governance within the distribution system remains a serious issue in food security programs, particularly rice. This study also suggested that the Collaborative Resilience (CORE) model can be implemented to address food security issues, especially in the rice distribution supply chain system in Banten Province.